2018
DOI: 10.18203/2319-2003.ijbcp20180105
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study in ophthalmology in OPD patients at a tertiary care teaching hospital

Abstract: Background: Drug therapy is a major component of patient care management in health care settings. Irrational and inappropriate use of drugs in health care system observed globally is being a major concern. In the field of ophthalmology, there have been many drug developments and different classes of drugs with combinational products are available in ophthalmology for the treatment of ophthalmic diseases. Periodic prescription analysis in the form of drug utilization study can improve the quality of prescriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
4
1
Order By: Relevance
“…Physicians may have been unwilling to prescribe medicines by generic name probably because it can lead to the purchasing of variable potency drugs and lower potent generic antibiotics which may contribute to drug resistance and instability in clinical response. The results obtained were contrary to study done by Bhatt JH et al 23 where 42.6% of medications were prescribed by generic name.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Physicians may have been unwilling to prescribe medicines by generic name probably because it can lead to the purchasing of variable potency drugs and lower potent generic antibiotics which may contribute to drug resistance and instability in clinical response. The results obtained were contrary to study done by Bhatt JH et al 23 where 42.6% of medications were prescribed by generic name.…”
Section: Discussioncontrasting
confidence: 99%
“…This serves as a measure of degree of polypharmacy. 20 and Mumbai (1.9) by Bhatt JH et al 23 showed lower number of drugs per prescription.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, the most commonly prescribed dosage formulation was eye drops in 89.12% of the prescriptions. A similar finding was reported in other studies done by Nehru M et al, 16 , Maniyar Y et al 20 , Bhatt JH et al, 21 and Akram MF et al 22 . The use of drops has the advantage of local action of the drug and minimizes the unwanted adverse drug effects that can occur with the use of systemic administration.…”
supporting
confidence: 90%
“…2 This necessitates a periodic review of pattern of drug utilization to ensure safe and effective treatment. 3 The principal aim of drug utilization research is to facilitate the rational use of drugs in populations. For the individual patient, the rational use of a drug implies the prescription of a well documented drug at an optimal dose, together with the correct information, at an affordable price.…”
Section: Introductionmentioning
confidence: 99%